Lithofacies and diagenetic controls on thrombolitic dolomite reservoir development from the Precambrian Dengying Formation in the central Sichuan Basin, SW China - Li, Yong; Zhang, Benjian; Zhou, Gang; Tang, Ruifeng; Long, Hongyu; Li, Chenglong; Chen, Xi; Chen, Di; Liu, Xiaohong; Zhang, Chao; Feng, Mingyou (Frontiers in Earth Science, 2024)
Microbialite reservoirs are of great importance in oil and gas exploration. However, there is still a lack of comprehensive studies on the formation mechanisms of thrombolitic reservoirs, a specific type of microbialite. This research focuses on the oldest thrombolitic dolomite reservoir located within the Precambrian Dengying Formation in the central Sichuan Basin, southwestern China. A multi-disciplinary approach was employed to characterize different thrombolite facies and elucidate the formation mechanism of thrombolitic dolomite reservoirs and their controlling factors, involving core observation, thin-section analysis, cathodoluminescence, scanning electron microscope (SEM) microscopy, elemental analysis using LA-ICP-MS, and carbon and oxygen stable isotope analysis. Based on variations in texture, four types of thrombolite were identified: 1) distinct clotted thrombolite, 2) diffuse and regular clotted thrombolite, 3) diffuse and irregular clotted thrombolite, and 4) composite clotted thrombolite. Notably, the diffuse clotted thrombolitic dolomite is the prevalent lithology in the reservoir. Through modification by meteoric water, organic acid fluids, and hydrothermal fluids, a reservoir with dominant porosity in the form of primary growth-framework pores, dissolution pores, and vugs was formed. This resulted in the development of two high-quality reservoir intervals within the Second Member and at the top of the Fourth Member of the Dengying Formation. The growth-framework porosity of the thrombolites, epigenetic karstification, and tectonic fracturing were mainly conducive to reservoir development. However, various types of cementation have reduced porosity and connectivity within the reservoir. Overall, this study is a valuable example of the methodology required to understand meso- and microstructures of deep-buried thrombolitic dolomite reservoirs, including their heterogeneities and diagenesis, as the original structures influence diagenesis.